An econometric analysis of financial distress determinants from an emerging economy governance perspective - Navitha Singh Sewpersadh (Cogent Economics & Finance, 2022)
During times of distress, companies are compelled to reassess operational policies and reengineer strategic formulations to discern value maximising uses for limited resources. The executive's agility to react to financial distress determines the probability of bankruptcy. Proper governance drives sound and sustainable, value maximising decision-making, while inept practices lead to value diminishing, self-serving behaviour that financially constrains companies, resulting in an acceleration of financial distress. This study examined the correlation between financial distress and corporate governance within a sample of 116 listed South African companies using the GMM estimation. Key financial distress determinants were found to be audit committees and shareholder activism (proxied by equity ownership) that may deter investor apathy, "director opportunism" and CEO dominance. Also, long-tenured CEOs and post-graduate directors possess contextually enriched latent knowledge that may assist distressed firms, particularly if the trade-offs between director's remuneration and governance is well managed. Furthermore, the K-score model served as a robust financial distress proxy since it allowed the interrogation of grey zone companies. These findings provided financial distress determinants aiding decision-making for ailing businesses to avoid liquidation, which can be of use to regulatory bodies and policymakers in developing sustainable governance strategies.
Keywords: E32; G32; G33; 330; Agency; CEO; corporate governance; directors; financial distress; shareholderactivism